German-Central European Supply Chain-Cluster Report : Staff Report, First Background Note, Second Background Note, Third Background Note. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses key findings of the Cluster Report on German-Central European Supply Chain (GCESC). Since the 1990s, a GCESC has evolved, manufacturing goods for export to the rest of the world. Reflecting this, bilateral trade linkages between Germany and the Czech Republic, Hungary, Poland, and the Slovak Republic (CE4) have expanded rapidly. Participation in the GCESC has led to technology transfers to CE4 countries and accelerated income convergence. Export growth in knowledge-intensive sectors has been particularly rapid in the CE4. It is also observed that complementarities between supply chain activities and domestic production have led to greater synchronization of the business cycle among GCESC countries.